2014
DOI: 10.4103/2231-0738.147461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight and obesity in urban school going adolescents in Shimla city

Abstract: Objectives:To study the prevalence of overweight and obesity among school going adolescents in Shimla city in Himachal Pradesh. Materials and Methods: A school based cross-sectional study was carried out to determine the prevalence of overweight and obesity among urban school-going adolescents (10 to 19 years) of both sexes studying from fifth to twelfth classes in various government and private schools of Shimla city in Himachal Pradesh. Results: A sample of 3385 students comprising 1665 females (49.2%) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…and (overweight/obesity in females: 65% and 77% resp). 14 In this study, the combined prevalence was found higher among those who were studying in private school (63%). The result was similar (65%) in a study conducted by Piryani et al in Nepal.…”
Section: Socio-demographic Factorsmentioning
confidence: 76%
“…and (overweight/obesity in females: 65% and 77% resp). 14 In this study, the combined prevalence was found higher among those who were studying in private school (63%). The result was similar (65%) in a study conducted by Piryani et al in Nepal.…”
Section: Socio-demographic Factorsmentioning
confidence: 76%
“…17 Overweight and obesity was more in girls 2.60% as compared to boys 1.2% in Shimla city. 18 This may be due to that during puberty, females have tendency to accumulate more fat. It is recognizing that weight gain during puberty is physiological so in puberty girls are more likely to overweight and obese as compare to boys.…”
Section: Discussionmentioning
confidence: 99%
“…20 In another study conducted at Shimla city, observed that the prevalence of overweight and obesity was 0.40% in the government schools and 3.40% in the private school children. 18 It may be due to children studying in private schools are not belonging to low socio-economic background which shows that high socio-economic status plays a major role in the contributing factor of overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Globally, obesity is called "New World Syndrome" which is causing severe economic and health burden on the community and the WHO defined it as a global epidemic in the past 20 years. [7,10] Prevalence of abdominal or central obesity is more in India as compared to other countries. [11] India is facing a new problem of normal weight obesity, wherein normal-weight individual, high body fat is seen over the viscera due to a sedentary lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Obesity is increasing significantly during the past two decades in India. [5][6][7] Overweight and obesity lead to approximately 2.8 million deaths in adults worldwide every year and are the fifth leading cause of mortality. [8] More than half of deaths in India occurred due to non-communicable diseases, and obesity is the root cause for so many non-communicable diseases.…”
Section: Introductionmentioning
confidence: 99%